2002
DOI: 10.1002/ls.3010140305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structure and metal atom of dialkyldithiophosphate derivatives on the wear behaviour in steel‐zirconia contacts

Abstract: Wear investigations concerning the different structures and metal atoms of metal dialkyldithiophosphates (MeDTPs) were conducted using a ball‐on‐disc apparatus. Steel ball bearings (3.175 mm in diameter) and counterface discs, made of hot pressed ZrO2 partially stabilised by Y2O3, were used. The synthesised MeDTPs were made up of primary linear aliphatic alcohols with hydrocarbon lengths varying from 8 to 16 carbon atoms, and contained the following metals: zinc(II), iron(III), gallium(III), antimony(III), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In a recent review on the history and action mechanism of ZnDTPs with metal surfaces (10), it is concluded that it has been so far proven impossible to identify any reasonably cost-effective compound having comparable antiwear properties to ZnDTPs lubricant additives. A survey of literature reveals that dialkyldithiophosphate esters (11), dialkyldithiophosphates of different metals such as molybdenum (12), cadmium (13), copper (14), titanium (15), gadolinium (16), iron, antimony, and other metals (17)(18)(19) have been introduced and used as multifunctional additives in lubricants. To the best of our knowledge, there are no open publications on boron dialkyldithiophosphates as additives in lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review on the history and action mechanism of ZnDTPs with metal surfaces (10), it is concluded that it has been so far proven impossible to identify any reasonably cost-effective compound having comparable antiwear properties to ZnDTPs lubricant additives. A survey of literature reveals that dialkyldithiophosphate esters (11), dialkyldithiophosphates of different metals such as molybdenum (12), cadmium (13), copper (14), titanium (15), gadolinium (16), iron, antimony, and other metals (17)(18)(19) have been introduced and used as multifunctional additives in lubricants. To the best of our knowledge, there are no open publications on boron dialkyldithiophosphates as additives in lubricants.…”
Section: Introductionmentioning
confidence: 99%